Factores de riesgos asociados al aborto en adolescentes atendidas en el Hospital Liborio Panchana Sotomayor, Santa Elena, octubre 2024 – febrero 2025. - López Pincay, Yixi Yixriana (2024)
Abortion in adolescents is a phenomenon that generates concern worldwide due to the implications it entails, therefore the present research aims to identify the risk factors associated with abortion in adolescents treated at the Liborio Panchana Sotomayor Hospital, Santa Elena, during the period october 2024 - february 2025. In order to fulfill the purpose of the research, a descriptive - correlational methodology has been implemented, with a mixed approach, of a cross-sectional type; its sample is made up of 138 adolescent patients treated at the health unit, for data collection the survey and documentary review techniques were used. The expected results of the research lie in identifying the risk factors that were mostly presented in the Hospital by those patients who had an abortion, and recognizing the complications that this health problem can generate.